Sensing Absence: How to See What Isn’t There in the Study of Science and Security - Rappert, Brian (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
Chapter 1 of this book is open access under a CC BY license. This is a chapter from Absence in Science, Security and Policy edited by Brian Rappert and Brian Balmer. This chapter is available open access under a CC BY license. Part reflection on the forthcoming chapters, part analysis of academic literature, and part programmatic agenda setting, this introduction chapter forwards the importance of questioning taken for granted assumptions in sensing what is absent as a concern. It undertakes this through initially examining what it means to characterize concern as absent or present in the first place. While absence and presence are often treated as binary opposites, it will be argued this distinction is difficult to sustain and unhelp for analysis. On the back of an appreciation of the inter-relation of absence and presence, this chapter then reviews the literature in sociology, ethics, STS and elsewhere relevant to the themes of the volume. A goal is to outline the methodological and epistemological possibilities and problematics of studying what is missing. By way of then proposing what is required, and to set the stage for the other chapters in Part 1, this chapter ends by asking how autostereograms provide a metaphor for viewing that can guide the study of absence.